Delineation of Functional Labour Market Regions—A Methodological Approach - Kropp, Per; Schwengler, Barbara (Raumforschung und Raumordnung | Spatial Research and Planning, 2011)
This paper proposes a methodological approach for delineating functional labour market regions based on commuter flows between German municipalities for the years 1993 to 2008 using the graph theory. The modularity commonly used in the analysis of networks is a suitable indicator of measuring the quality of delineations. We present a delineation of 50 labour market regions of quite different sizes that is robust for all years in the analysis. A further delineation based on commuter flows between districts is nearly as good in measuring the employment self-containment-ratio as the delineation based on commuter flows between municipalities. Comparing the presented delineation with former delineations for Germany by different statistical measures confirms the quality of the result.